Congenital isolated clubfoot: Correlation between prenatal assessment and postnatal degree of severity - Lanna, Mariano; Casati, Daniela; Torre, Clelia; Monforte, Sergio; Andreacchio, Antonio; Faiola, Stefano; Cetin, Irene; Rustico, MariaAngela (Prenatal diagnosis, 2020)
Objective Since prenatal diagnosis of isolated clubfoot has a false positive rate (FP) of 10%‐40%, fetal parameters that might correlate with post‐natal confirmation and grade of severity were investigated. Method Retrospective analysis (2013‐2019) of cases analysed with three‐dimensional multiplanar view. The following data were recorded: the angle between the long axis of foot and lower leg; width, length and width‐to‐length ratio (W/L) of the foot; tibia length and calf width (T/C) ratio. Severity after birth was assessed using the Pirani classification. Results Diagnosis was confirmed in 45/53 neonates (84.9%, FP 15%). Values were higher for both angle and W/L in true vs false positive cases (median angle 100.4° versus 69.55°, p <.000; median W/L 0.53 vs 0.45, p = .001), no difference for T/C (3.77 vs 3.48, p = .8). The area under the curve for angle was 0.98 (CI 0.94‐1.00), with a diagnostic cut‐off of 84.7° (PPV of 100%, NPV of 66.7%). Median Pirani score, available for 33 neonates (73.3%) was 3 (IQR 3‐4): only angle correlated with Pirani score (Spearman coefficient 0.36, p = .04) Conclusion Measuring the angle between the foot and lower leg can reduce the FP rate of prenatal congenital clubfoot diagnosis and better predict the need for postnatal treatment.